ARCHITECTURE CHANCAY. THE TINKUY IN SPACE ORGANIZATION - Guzmán Juárez, Miguel (2015)
Little is known of the architecture of the old society Chancay. From surveys architectural plans have been developed in different buildings and has built a perceptual image of the organization and structure of space corresponding to certain cultural norms. It was possible to correlate the organization of buildings with certain forms of thought raised to the Andean societies, such as the criteria of duality, tripartition and complementarity among others. Pisquillo Chico particularly remarkable and his ceremonial sector, where building a recurring pattern that identifies this society is defined. It is postulated that the “ramp building” becomes social archetype, a symbolization materials three-dimensional (architectural) of the logic of reciprocity and the meeting of opposites through an investment of, inside the wonderful Andean concept that refers the tinkuy.